Classical Islam - Hillenbrand, Carole, 1943- (Edinburgh)
xvii, 438 sayfa, [32] sayfa resim
Keywords: “Classical Islam presents studies of the career of the Prophet Muhammad and the environment from which he sprang; the evolution of Islamic mysticism; political thought; and philosophical themes. It also includes investigations into the development of the late ‘Abbasid caliphate; analyses of the Mirror for Princes literature; and studies of the minor dynasties of Iraq and Anatolia, and of the major cities in the region.” --